Du naturalisme au naturisme : mutations idéaliste et identitaire à travers l’oeuvre du peintre belge Léon Frederic (1856–1940) - Foudral, Benjamin (RACAR : Revue d'art canadienne / Canadian Art Review, 2016)
In an article published in 1895 in the Belgian periodical L’Art Jeune, the writer and art critic Henri Vandeputte introduced the artist Léon Frederic — whom he called “le Premier des peintres belges”— as the leading figure of a new artistic neologism : naturisme. This is one instance that points to the consistent critical extrapolation and ideological exploitation of Frederic and his unclassifiable paintings. This article focuses on the reception of Frederic’s work in order to understand how artistic terms such as réalisme, naturalisme, and naturisme were used in the name of a nationalist art history in which Belgian art could both claim the legacy of Flemish art and detach itself from the dominant model of French art.